2013
DOI: 10.1186/1617-9625-11-13
|View full text |Cite
|
Sign up to set email alerts
|

The role of tobacco use on dental care and oral disease severity within community dental clinics in Japan

Abstract: BackgroundTo examine facilitators of dental smoking intervention practices in Japan, where smokeless tobacco is rarely used, we evaluated the characteristics of dental care for smokers.MethodsCommunity dentists volunteered to record the treated disease or encounter with patients that was principally responsible for their dental care on the survey day. Patients were classified into groups receiving gingival/periodontal treatment (GPT), caries/endodontic treatment (CET), prosthetic treatment (PRT), periodical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Along with lung cancer, vascular stenosis, heart attacks and periodontal disease, dental caries has been reported to be associated with smoking all over the world, including Swedish and US smokers, Mexican truck drivers, Turkey and Japanese children, and Italy military personnel (4)(5)(6)(7)(8)(9). A recent study in Japan demonstrated smokers received more caries/endodontic treatment than non-smokers (10).…”
Section: Introductionmentioning
confidence: 99%
“…Along with lung cancer, vascular stenosis, heart attacks and periodontal disease, dental caries has been reported to be associated with smoking all over the world, including Swedish and US smokers, Mexican truck drivers, Turkey and Japanese children, and Italy military personnel (4)(5)(6)(7)(8)(9). A recent study in Japan demonstrated smokers received more caries/endodontic treatment than non-smokers (10).…”
Section: Introductionmentioning
confidence: 99%
“…25 However, the detrimental effects of smoking may not be clearly realized by dental professionals, unless the smoking status of all patients is identified. 26 Furthermore, as shown by a survey conducted in European dental schools, education opportunities for tobacco cessation should be strengthened within undergraduate dental education 27 and by continuing professional development.…”
Section: Discussionmentioning
confidence: 99%
“…, , Ojima et al . ). Finally, two reports concluded that endodontic treatment in smokers had fewer successes (Doyle et al .…”
Section: Association Between Endodontics and Smoking Habitsmentioning
confidence: 97%
“…Ojima et al . () studied the characteristics of dental care of 2835 current smokers and 6850 nonsmokers finding that caries/endodontic treatment were significantly more frequent in smokers compared to nonsmokers (47.1% vs. 43.6%, P = 0.002).…”
Section: Association Between Endodontics and Smoking Habitsmentioning
confidence: 99%
See 1 more Smart Citation